Colebrooke, Nesbitt, Colebrooke & Franks records - Colebrooke, Nesbitt, Colebrooke & Franks
Correspondence, letter drafts, contracts, audit requests, memorandum book, and bound and unbound account books pertaining to contracts for the supply of provisions to British forces in America.
British mercantile firm of James Colebrooke, Arnold Nesbitt, George Colebrooke, and Moses Franks, suppliers of food to British troops in North America.
Collection material in English.
Keywords: Colebrooke, George, -- Sir, -- 1729-1809.; Colebrooke, James; Franks, Moses, -- 1719-1789.; Nesbitt, Arnold; Great Britain. -- Army -- Colonial forces -- America; Great Britain. -- Army -- Supplies and stores; Merchants -- Great Britain; United States -- History -- French and Indian War, 1754-1763 -- British forces; United States -- History -- Revolution, 1775-1783 -- British forces